2018
DOI: 10.1002/bjs5.45
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the cost-effectiveness of preoperative antibiotic prophylaxis in reducing surgical-site infection

Abstract: BackgroundSurgical‐site infections (SSIs) increase the length of hospital admission and costs. SSI prevention guidelines include preoperative antibiotic prophylaxis. This review assessed the reporting quality and cost‐effectiveness of preoperative antibiotics used to prevent SSI.MethodsPubMed, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Index of Economic Articles (EconLit), Database of Abstracts of Reviews of Effect (including the National Health Service Economic Evaluation Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 62 publications
3
16
0
3
Order By: Relevance
“…Our previously published data first revealed a CSD prevalence of 43.4% (95% CI 39.1% to 47.7%, n=514) in Shanghai, which is a cause for concern 17. Our cohort study also showed that infection might be an important risk factor for CSD and that multidose antibiotic administration has a significant protective effect compared with single-dose antibiotic administration (CSD prevalence 31.1%, 95% CI 23.8% to 38.3% vs 49.0%, 95% CI 43.8% to 54.3%; aOR=0.4, 95% CI 0.3 to 0.7) 18–20. Furthermore, the single-dose cefuroxime subgroup (n=190) was found to have a significantly lower CSD prevalence than the single-dose cefradine subgroup (n=162) (38.9%, 95% CI 34.7% to 48.6% vs 56.8%, 95% CI 51.3% to 66.7%; aOR=0.5, 95% CI 0.3 to 0.8, p=0.006).…”
Section: Introductionsupporting
confidence: 51%
“…Our previously published data first revealed a CSD prevalence of 43.4% (95% CI 39.1% to 47.7%, n=514) in Shanghai, which is a cause for concern 17. Our cohort study also showed that infection might be an important risk factor for CSD and that multidose antibiotic administration has a significant protective effect compared with single-dose antibiotic administration (CSD prevalence 31.1%, 95% CI 23.8% to 38.3% vs 49.0%, 95% CI 43.8% to 54.3%; aOR=0.4, 95% CI 0.3 to 0.7) 18–20. Furthermore, the single-dose cefuroxime subgroup (n=190) was found to have a significantly lower CSD prevalence than the single-dose cefradine subgroup (n=162) (38.9%, 95% CI 34.7% to 48.6% vs 56.8%, 95% CI 51.3% to 66.7%; aOR=0.5, 95% CI 0.3 to 0.8, p=0.006).…”
Section: Introductionsupporting
confidence: 51%
“…Recently completed and ongoing research studies to find the most cost-effective prevention strategies for SSI, are having mixed success [13,14]. The majority of this research is randomised controlled trials (RCTs) with a parallel economic evaluation based in HIC [15,16]. Plans are in place to carry out similar studies exploring cost-effective strategies to combat SSI in the LMIC setting [17].…”
Section: Introductionmentioning
confidence: 99%
“…The global variability of healthcare systems, financial structures, currencies, local epidemiologic data, and resistance patterns have limited the generalizability and the comparability of the economic evidence between countries [13]. This has highlighted the urgent need for high-quality studies using a standardized methodology for the evaluation of the economic burden of SSI [6, 63]. Literature review has shown that the major limitations in these studies are mainly related to (1) the uses of different definitions to classify SSI [7] and to the inability to follow-up with patients long enough post-surgical discharge [64].…”
Section: Resultsmentioning
confidence: 99%
“…Limitations in the methods of economic evaluation may also be related to (3) the location and settings were the study was conducted (i.e. Studies grouped into the same surgical specialty may not be comparable due to differences in operating theater conditions and surgical procedures [13, 63]). Some studies assigned the development of SSI to multiple or unspecified surgeries which can be a source of bias, limiting the comparability of data.…”
Section: Resultsmentioning
confidence: 99%